Diaphragm and preparation method thereof, battery and electric device

CN119487691APending Publication Date: 2025-02-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202380051159.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-01-06
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Lithium-ion batteries are prone to oxidative decomposition and heat release under high temperatures and pressures, leading to thermal runaway. Moreover, existing modified separators cannot block the heat release reaction inside the battery in time, reducing the safety performance of the battery.

Method used

A polymer particle coating is set on the base film. The melting point of the polymer particles is 90°C to 120°C. When the temperature rises, it melts and seals the pores of the base film to prevent chemical reactions and maintain good breathability in environments below the melting point. properties to ensure lithium ion transfer.

Benefits of technology

It effectively reduces the risk of battery thermal runaway, improves the safety performance and electrochemical performance of the battery, and ensures the charge and discharge performance of lithium-ion batteries in normal operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119487691A_ABST
    Figure CN119487691A_ABST
Patent Text Reader

Abstract

The invention discloses a diaphragm and a preparation method thereof, a battery and an electric device. The diaphragm comprises a base membrane and a coating arranged on at least one surface of the base membrane, the coating contains polymer particles, and the melting point of the polymer particles is 90-120 DEG C. The diaphragm provided by the embodiment of the invention contains the coating, and can be melted at the melting point temperature of polymer particles and seal pores contained in the base membrane, so that the thermal runaway risk of the battery is reduced, and the safety performance of the battery is improved. The preparation method can ensure stable performance of the diaphragm structure and the like. The battery comprises the diaphragm.
Need to check novelty before this filing date? Find Prior Art

Description

Diaphragm and preparation method thereof, battery and electrical device Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a diaphragm and a preparation method thereof, a battery, and an electrical device. Background Art

[0002] In the context of energy conservation and emission reduction, new energy technologies are developing rapidly, among which the research breakthroughs and applications of battery technology are the most significant, and lithium-ion batteries are the battery with the most prominent development momentum.

[0003] As battery applications expand, especially in recent years with the rapid development of electric vehicles, power batteries have experienced rapid development and a sharp increase in demand. However, battery safety performance has also received increasing attention and has become one of the key factors restricting the expansion of battery applications.

[0004] Among battery safety issues, the most prominent is the runaway exothermic reaction within the battery. Specific causes include: the formation of lithium dendrites on the negative electrode surface, which can pierce the separator and cause a short circuit; external damage to the battery, causing a short circuit; and the oxidation and decomposition of the electrolyte under high temperature and high pressure, which releases a large amount of heat and triggers thermal runaway. These exothermic reactions can cause a sharp increase in the temperature and pressure within the battery. If the heat is not released in a timely manner, it can easily lead to thermal runaway, causing the battery to burn or even explode.

[0005] Summary of the Invention

[0006] In view of the above problems, the embodiments of the present application provide a diaphragm and a preparation method thereof, a battery, and an electrical device to improve the electrochemical performance and safety performance of the diaphragm in battery production or operation.

[0007] In a first aspect, embodiments of the present application provide a separator comprising a base film and a coating disposed on at least one surface of the base film, the coating containing polymer particles having a melting point of 90°C to 120°C, optionally 100°C to 115°C.

[0008] The coating of the separator of the embodiment of the present application contains polymer particles with this melting point range, which can melt when the melting point is reached, thereby sealing the pores contained in the base film, preventing or reducing chemical reactions within the battery, including crosstalk reactions between the positive and negative electrodes of the battery, thereby reducing the risk of thermal runaway of the battery and improving battery safety performance. On this basis, the polymer particles can give the separator good air permeability in an environment below the melting point temperature, which can effectively ensure the transfer of lithium ions between the positive and negative electrodes during normal operation of the battery, thereby significantly improving the electrochemical performance and safety performance of the battery.

[0009] In some embodiments, the polymer particles satisfy at least any one of the following conditions (1) to (5):

[0010] (1) Volume distribution particle size D of the polymer particles v 50 is 0.1μm to 5μm, optionally 0.3μm to 3μm;

[0011] (2) The morphology of the polymer particles includes at least one of chain, spherical, quasi-spherical, fibrous, tubular, rod-like, amorphous, and pyramidal;

[0012] (3) The polymer material of the polymer particles contains non-ionic groups, and optionally, the non-ionic groups include at least one of ethoxy, hydroxyl, and carboxylate groups;

[0013] (4) The weight average molecular weight of the polymer of the polymer particles is 1,000 to 10,000, and can be optionally 1,500 to 8,000;

[0014] (5) The polymer of the polymer particles includes at least one of polystyrene, polyolefin, polyimide, melamine resin, phenol resin, cellulose, polyester, polyphenylene sulfide, polyaromatic amide, polyamideimide, copolymer of butyl acrylate and ethyl methacrylate, and modified polymers thereof.

[0015] The polymer particles possess any of the aforementioned characteristics, improving their dispersibility. This improves the air permeability of the coating, thereby enhancing the air permeability of the separator, in environments with temperatures below the melting point of the polymer particles. Furthermore, in environments with temperatures near the melting point of the polymer particles, the membrane's melting response to abnormal temperature increases is enhanced. Specifically, when the polymer material of the polymer particles contains nonionic groups, this improves the dispersion of the polymer particles in the coating, increasing the uniformity of the coating and thereby improving the overall air permeability of the separator.

[0016] In some embodiments, the coating further comprises an inorganic particle filler. The presence of the inorganic particle filler can improve the air permeability and stability of the separator, and can also improve the mechanical properties of the separator, such as heat shrinkage resistance.

[0017] In some embodiments, the inorganic particulate filler satisfies at least one of the following conditions:

[0018] The dry weight ratio of the inorganic particulate filler to the polymer particles is (15 to 25): (25 to 35);

[0019] The volume distribution particle size D of the inorganic particle filler v 50 is 1μm to 1.5μm;

[0020] The inorganic particle filler includes at least one of inorganic particles having a dielectric constant of 5 or greater, inorganic particles having ion conductivity but not storing ions, and inorganic particles capable of undergoing electrochemical reactions.

[0021] The inorganic particle filler has any of the above characteristics and can further improve the mechanical properties of the diaphragm, such as air permeability and heat shrinkage resistance.

[0022] In an exemplary embodiment, the polymer contained in the polymer particles is low-density polyethylene. In an exemplary embodiment, the low-density polyethylene is non-ionic low-density polyethylene.

[0023] The low-density polyethylene particles or the nonionic low-density polyethylene particles can further enhance the synergistic effect of the air permeability between the polymer particles and the inorganic particles as shown above, and can also enhance the liquid absorption and storage capacity of the membrane.

[0024] In some embodiments, the coating layer further comprises a binder. By adding the binder to the coating layer, the mechanical strength of the diaphragm can be improved and the air permeability and stability of the diaphragm can be adjusted.

[0025] In the embodiment, the binder satisfies at least any one of the following conditions:

[0026] The dry weight ratio of the binder to the polymer particles is (15 to 25): (25 to 35);

[0027] The binder is a water-based binder;

[0028] The thermal decomposition temperature of the binder is higher than 160°C;

[0029] The binder includes at least one of polyvinyl alcohol, polyacrylic acid-polyacrylonitrile copolymer, polyacrylate-polyacrylonitrile copolymer, polyether acrylate, polyurethane, polyacrylate, polycarbonate, polyethylene oxide, rubber, polyacrylic acid, polyacrylonitrile, gelatin, chitosan, sodium alginate, cyanoacrylate, polymerized cyclic ether derivatives, and hydroxyl derivatives of cyclodextrin.

[0030] The adhesive has any of the above characteristics and can further enhance the mechanical properties of the coating contained in the diaphragm and the base film, thereby improving the air permeability and stability of the diaphragm.

[0031] In some embodiments, the coating has a thickness of 2 μm to 5 μm.

[0032] In some embodiments, the coating is disposed on one surface of the base film.

[0033] By adjusting the coating thickness and the position on the base film, the permeability of the coating (i.e., the diaphragm) and the wettability and storage capacity of the electrolyte are improved, thereby reducing the risk of thermal runaway of the battery.

[0034] In some embodiments, the base film satisfies at least one of the following conditions:

[0035] The base film has a thickness of 4 μm to 7 μm;

[0036] The air permeability of the base film is 180s / 100cc to 240s / 100cc;

[0037] The material of the base film includes at least one of non-woven fabric, polyolefin, polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene oxide, polyphenylene sulfide, and polyethylene naphthalene.

[0038] The base film with these characteristics not only fully exerts the role of the battery separator, but also improves the mechanical properties such as compressive resistance and air permeability of the separator.

[0039] In a second aspect, an embodiment of the present application provides a method for preparing a diaphragm. The method for preparing a diaphragm in an embodiment of the present application comprises the following steps:

[0040] providing a basement membrane;

[0041] Providing a coating slurry, wherein the coating slurry contains polymer particles, and the melting point of the polymer particles is 90° C. to 120° C., optionally 100° C. to 115° C.;

[0042] The coating slurry is coated on at least one surface of the base film, and dried to form a coating layer to obtain a separator.

[0043] The diaphragm prepared by the diaphragm preparation method of the embodiment of the present application has good air permeability and stability as the diaphragm of the embodiment of the text application above, while effectively reducing the risk of thermal runaway of the battery and improving the electrochemical performance and safety performance of the battery.

[0044] In some embodiments, the coating slurry is formed by mixing polymer particles, inorganic particle fillers and binders in a solvent; wherein the mass ratio of the polymer particles, inorganic particle fillers and binders in the coating slurry is (25 to 35): (15 to 25): (15 to 25).

[0045] In some embodiments, the coating slurry has a solid content of 30 wt % to 40 wt %.

[0046] In some embodiments, the coating slurry has a viscosity of 100 mPa·s to 1000 mPa·s at 25°C.

[0047] The coating slurry having the above characteristics can improve the film-forming quality, the quality of the coating and the performance such as the air permeability.

[0048] In some embodiments, when the polymer particles are polymer particles containing nonionic groups, the polymer particles are prepared by a method comprising the following steps:

[0049] The polymer precursor particles, the ethoxy-containing polymer and the initiator are mixed and reacted to obtain polymer particles containing nonionic groups;

[0050] The polymer particles containing nonionic groups are emulsified with a nonionic surfactant to obtain a nonionic polymer emulsion.

[0051] By using ethoxylated polymers to carry out polymerization reactions with polymer precursor particles, the nonionic groups contained in the polymer particles can be increased, especially the processing performance of the polymer particles can be improved, thereby improving the dispersibility of the polymer particles in the coating slurry, thereby improving the film-forming quality of the coating slurry, and improving the air permeability and other properties of the coating.

[0052] In some embodiments, the polymer precursor particles, the ethoxy-containing polymer, and the initiator are mixed in a mass ratio of (300 to 400): (90 to 125): (20 to 100).

[0053] In some embodiments, the material of the polymer precursor particles includes at least one of polystyrene, polyolefin, polyimide, melamine resin, phenol resin, cellulose, polyester, polyphenylene sulfide, polyaramid, polyamideimide, and a copolymer of butyl acrylate and ethyl methacrylate.

[0054] In some embodiments, the ethoxy-containing polymer includes at least one of allyl polyethylene glycol and bisallyl polyether.

[0055] In some embodiments, the initiator includes at least one of di-tert-butyl peroxide and dicumyl peroxide.

[0056] In some embodiments, the reaction temperature may be 130°C to 160°C.

[0057] In some embodiments, the polymer particles and the nonionic surfactant are emulsified in a mass ratio of (4 to 6):1.

[0058] The above-mentioned reactant types, mixing ratios and reaction conditions can increase the non-ionic group grafting rate and content of the polymer particles, improve the processing performance and dispersibility of the polymer particles, and thus improve the film-forming quality of the coating slurry and the air permeability of the formed coating.

[0059] In the embodiment, the nonionic polymer emulsion satisfies at least any one of the following conditions (1) to (4):

[0060] (1) The viscosity of the nonionic polymer emulsion at 25° C. is 10 mPa·s to 100 mPa·s;

[0061] (2) the solid content of the nonionic polymer emulsion is 35 wt% to 40 wt%;

[0062] (3) the pH value of the nonionic polymer emulsion is 5 to 6;

[0063] (4) The nonionic surfactant includes a molecular structure of Wherein, R1 is a carbon chain alkyl group, R2 is a hydrophilic group, and n is a positive integer from 3 to 20.

[0064] In an exemplary embodiment, the carbon chain alkyl group is a long carbon chain alkyl group ranging from C12 to C18.

[0065] In an exemplary embodiment, R2 is at least one of a carboxyl group, an amine group, an aldehyde group, an alcohol group, an amino group, and an amide group.

[0066] In an exemplary embodiment, the nonionic surfactant includes at least one of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester, castor oil polyoxyethylene ether, fatty amine polyoxyethylene ether, sorbitan fatty acid ester, and polyoxyethylene sorbitan fatty acid ester.

[0067] By selecting the type of nonionic surfactant, the stability of the nonionic polymer emulsion can be improved, its dispersibility in the coating slurry and the stability of the coating slurry can be improved, thereby improving the quality and air permeability of the formed coating.

[0068] In some embodiments, the binder is added in the form of a binder aqueous solution, and the binder aqueous solution has at least one of the following conditions:

[0069] The viscosity of the binder aqueous solution is 3000 mPa·s to 10000 mPa·s;

[0070] The solid content of the binder aqueous solution is 40 wt % to 50 wt %.

[0071] In some embodiments, the coating slurry is applied at a rate of 50 m / min to 100 m / min; and / or

[0072] The drying temperature is 60°C to 70°C; and / or

[0073] The drying time is 1 min to 3 min.

[0074] By adjusting the coating process conditions, the film quality, thickness and permeability can be adjusted and optimized.

[0075] In a third aspect, embodiments of the present application provide a battery. The battery of the present application embodiment includes a positive electrode, a negative electrode, and a separator laminated between the positive and negative electrodes, wherein the separator is the separator described in the present application embodiment or a separator prepared by the separator preparation method of the present application embodiment. Because the battery of the present application embodiment includes the separator of the present application embodiment, the battery has high safety and good electrochemical properties such as capacity retention.

[0076] In an embodiment, the coating is provided on one surface of the separator, with the coating facing the negative electrode. By only applying the coating to one surface of the separator, the overall thickness of the separator can be effectively reduced, thereby increasing the energy density of the battery.

[0077] In a fourth aspect, an embodiment of the present application provides an electrical device, wherein the electrical device includes a battery according to an embodiment of the present application, and the battery is used to provide electrical energy. The safety of the electrical device according to the embodiment of the present application is significantly improved.

[0078] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, which can be implemented in accordance with the contents of the specification, and to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0079] Various other advantages and benefits will become apparent to those skilled in the art upon reading the detailed description of the preferred embodiment below. The accompanying drawings are for illustration purposes only and are not to be considered as limiting the present application. The same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0080] FIG1 is a schematic flow chart of a method for preparing a diaphragm according to an embodiment of the present application;

[0081] FIG2 is a schematic structural diagram of an embodiment of a secondary battery according to an embodiment of the present application;

[0082] FIG3 is an exploded schematic diagram of the secondary battery shown in FIG2 ;

[0083] FIG4 is a schematic structural diagram of an embodiment of a battery module according to the present application;

[0084] FIG5 is a schematic structural diagram of an embodiment of a battery pack according to the present application;

[0085] FIG6 is a schematic diagram of the exploded structure of the battery pack shown in FIG5 ;

[0086] FIG7 is a schematic diagram of an embodiment of an electric device including a secondary battery according to an embodiment of the present application as a power source;

[0087] FIG8 is a scanning electron microscope (SEM) image of the diaphragm in Example A1 of the present application; FIG8 is a SEM image of the diaphragm at room temperature, and FIG8 is a SEM image of the diaphragm after being heated at 130° C. for 15 minutes;

[0088] Figure 9 is a scanning electron microscope (SEM) image of the diaphragm in comparative example A1 of the present application; wherein, Figure a is a SEM image of the diaphragm at room temperature, and Figure b is a SEM image of the diaphragm after being heated at 130°C for 15 minutes.

[0089] The accompanying drawings in the specific implementation manner are as follows:

[0090] 10. Secondary battery cell, 11. Housing, 12. Electrode assembly, 13. Cover plate;

[0091] 20. Battery module;

[0092] 30. Battery pack, 31. Box, 32. Lower box. DETAILED DESCRIPTION

[0093] The following embodiments of the technical solution of the present application will be described in detail with reference to the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application and are therefore only examples and are not intended to limit the scope of protection of the present application.

[0094] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification and claims of this application and the above-mentioned figure descriptions are intended to cover non-exclusive inclusions.

[0095] In the description of the embodiments of this application, the technical terms "first" and "second" are used only to distinguish different objects and should not be understood to indicate or imply relative importance or implicitly specify the quantity, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, the meaning of "plurality" is more than two, unless otherwise clearly and specifically defined.

[0096] References herein to "embodiments" mean that a particular feature, structure, or characteristic described in connection with the embodiments may be included in at least one embodiment of the present application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor does it constitute an independent or alternative embodiment that is mutually exclusive of other embodiments. It is understood, both explicitly and implicitly, by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0097] In the description of the embodiments of this application, the term "and / or" is simply a description of the association relationship between associated objects, indicating that three relationships can exist. For example, A and / or B can represent the following three situations: A exists alone, A and B exist simultaneously, and B exists alone. In addition, the character " / " in this document generally indicates that the associated objects are in an "or" relationship.

[0098] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0099] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc., indicating the orientation or position relationship, are based on the orientation or position relationship shown in the accompanying drawings, and are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the embodiments of the present application.

[0100] In the description of the embodiments of the present application, unless otherwise expressly specified or limited, technical terms such as "installed," "connected," "connected," and "fixed" should be understood in a broad sense. For example, they can refer to fixed connections, detachable connections, or integration; mechanical connections or electrical connections; direct connections or indirect connections through an intermediate medium; internal connections between two components or interactions between two components. Those skilled in the art can understand the specific meanings of the above terms in the embodiments of the present application based on specific circumstances.

[0101] In the context of energy conservation and emission reduction, new energy technologies are developing rapidly, among which the research breakthroughs and applications of battery technology are the most significant, and lithium-ion batteries are the battery with the most prominent development momentum.

[0102] In ion batteries such as lithium-ion batteries, the diaphragm is one of the important components, which is set between the positive and negative pole pieces to separate the positive and negative poles of the battery, preventing the two poles from contacting and short-circuiting, and preventing the Li-ion battery from passing through the positive and negative poles. + Therefore, in addition to having good electrolyte wettability, liquid retention, and mechanical strength, the separator also needs to have properties such as thermal stability that have a significant impact on battery safety, as battery safety performance is increasingly valued.

[0103] Currently, the method of improving the thermal stability and other properties of the diaphragm is to modify the diaphragm, such as doping or coating modifiers such as flame retardant additives, fiber-like substances, electrochemically inert ceramics, etc. during the preparation process of the diaphragm, so as to achieve the purpose of improving the thermal stability and other properties of the diaphragm and thus improving battery safety.

[0104] While current methods like doping or coating can improve separator performance, such as thermal stability, to a certain extent, the inventors discovered during their research that when exothermic reactions within the battery accumulate to a certain level, the modified separator is unable to promptly block the continued reaction, making it difficult to slow the exothermic reaction and reduce the likelihood of internal short circuits or even thermal runaway. Therefore, their effectiveness in improving battery safety, such as thermal runaway, is unsatisfactory.

[0105] To improve the separator's ability to suppress thermal runaway, current methods include modifying the separator surface, such as adding a modified coating. However, the inventors discovered that adding a modified coating to the separator can negatively impact the separator's air permeability. Furthermore, when the battery is subjected to stress during assembly and normal operation, the modified coating reduces the separator's air permeability, thereby reducing the separator's permeability to the electrolyte. This further degrades the battery's electrochemical properties, such as cycling performance, and affects the battery's normal operation and performance.

[0106] Therefore, in order to reduce the risk of thermal runaway of the battery, improve the safety performance of the battery, and improve the air permeability and stability of the diaphragm, the inventors found through research that adding a coating containing polymer particles to the diaphragm ensures good air permeability of the diaphragm and ensures good air permeability and stability during normal production and use of the battery; when overheating occurs inside the battery, the coating can also melt and seal the pores of the diaphragm in time to form a blocking barrier layer, reducing or completely blocking the reaction inside the battery, thereby reducing the risk of thermal runaway of the battery and improving the safety performance of the battery.

[0107] diaphragm

[0108] In a first aspect, embodiments of the present application provide a separator. The separator includes a base film and a coating disposed on at least one surface of the base film. The coating contains polymer particles having a melting point of 90°C to 120°C.

[0109] In the separators of the present invention, the base film comprises the substrate and performs the usual functions of a separator. The coating is applied to the base film and modifies the base film, i.e., the separator matrix. For example, when the temperature reaches between 90°C and 120°C, the polymer particles melt and seal the pores in the base film.

[0110] The melting point of the polymer particles contained in the coating of the separator of the embodiment of the present application is 90°C to 120°C. When the temperature inside the battery rises abnormally to the melting point of the polymer particles, the polymer particles can melt in time and seal the pores contained in the base film. When the polymer particles melt and seal the pores contained in the base film, the separator acts as a barrier, thereby effectively reducing or preventing chemical reactions inside the battery, including chemical reactions in the electrolyte, migration of metal ions, and positive and negative electrode crosstalk reactions, thereby alleviating or terminating thermal runaway and improving the safety performance of the battery. Among them, the migration of metal ions includes lithium ions and metal precipitation from active materials, etc., to prevent them from passing through the separator and depositing on the surface of the electrode, especially the negative electrode, or further forming dendrites. Positive and negative electrode crosstalk reaction refers to the release of oxygen when the positive electrode active material undergoes a phase change at high temperature. Oxygen can diffuse through the separator to the negative electrode and react with the negative electrode, etc., and release a large amount of heat; it also includes hydrogen released from the negative electrode at high temperature, which diffuses through the separator to the positive electrode and reacts with the positive electrode, etc., and releases a large amount of heat.

[0111] Furthermore, because the polymer particles within this melting point range exist in a granular morphology, they impart excellent air permeability to the coating, or separator. Furthermore, during normal battery production and use, the separator ensures good transfer of lithium ions in the electrolyte between the positive and negative electrodes, thereby improving the battery's electrochemical performance, including charge-discharge and cycling performance.

[0112] Therefore, the polymer particles having a melting point of 90°C to 120°C, optionally 100°C to 115°C, and in exemplary embodiments, typical but non-limiting melting points such as 90°C, 92°C, 94°C, 96°C, 98°C, 100°C, 102°C, 104°C, 106°C, 108°C, 110°C, 112°C, 115°C, 117°C, and 120°C, have a coating with good air permeability, and can ensure good air permeability of the diaphragm during battery production and normal operation, thereby ensuring the normal electrochemical performance of the battery. The inventors have found that if the melting point is too low, such as below 90°C, or too high, such as above 120°C, the coating formed by the polymer particles will reduce the air permeability of the diaphragm, thereby reducing the air permeability of the diaphragm during battery production or normal operation, thereby reducing the electrochemical performance of the battery under normal operation. Moreover, when the melting point is lower than 90°C, the polymer particles will melt during normal operation of the battery, thereby affecting the electrochemical performance of the battery; or when the melting point of the polymer particles is too high, such as higher than 120°C, the thermal sensitivity of the coating will decrease or even fail, resulting in the inability to melt in time to seal the pores of the base membrane when the battery thermally runs away.

[0113] In some embodiments, the polymer particles contained in the coating may have at least one of the following morphologies: chain, spherical, quasi-spherical, fibrous, tubular, rod-shaped, amorphous, and pyramidal. These polymer particles can enhance the air permeability of the coating, or separator, during normal battery operation, improving the battery's electrochemical performance. When the battery's internal temperature rises abnormally to the polymer particle melting point, these particles can increase the melting rate, accelerating the closure of the basement membrane pores. Consequently, these polymer particles can further reduce the risk of thermal runaway and enhance battery safety.

[0114] In some embodiments, the volume distribution particle size D of the polymer particles contained in the coating is v 50 can be 0.1 μm to 5 μm, optionally 0.3 μm to 3 μm, and in exemplary embodiments, can be 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, and other typical but non-limiting particle sizes. By controlling the particle size of the polymer particles within this range, the uniformity of the distribution of the polymer particles in the coating can be improved, the air permeability of the separator can be improved, and the hot melt response rate of the coating can also be increased.

[0115] In some embodiments, the polymer material of the polymer particles in the above embodiments contains non-ionic groups. In the exemplary embodiments, the non-ionic group may include at least one of an ethoxy group, a hydroxyl group, and a carboxylate group. The material of the polymer particles contains non-ionic groups, specifically non-ionic groups of these types, which can improve the hydrophilicity and dispersibility of the polymer particles, thereby improving the uniformity of the polymer particles in the coating, thereby further improving the air permeability of the coating, thereby improving the good air permeability of the diaphragm during battery production and normal operation, and improving the transferability of lithium ions between the positive and negative electrodes, so as to improve the volatilization effect of the above-mentioned effects of the diaphragm in the embodiment of the present application. In the embodiment, the non-ionic group can be a grafted side chain of the polymer, or it can be connected to the main chain of the polymer.

[0116] In some embodiments, the polymer material of the polymer particles in the above embodiments may be a polymer with a weight average molecular weight of 1000 to 10000, optionally 1500 to 8000. In the exemplary embodiment, the polymer may include at least one of polystyrene, polyolefin, polyimide, melamine resin, phenol resin, cellulose, polyester, polyphenylene sulfide, polyaromatic amide, polyamide-imide, copolymer of butyl acrylate and ethyl methacrylate, and their respective modified polymers. By selecting the polymer material of the polymer particles, such as selecting these polymers, the melting point of the polymer particles in the above embodiments can be effectively controlled in the range of 90°C to 120°C, and the hot melt response rate of the polymer particles can be further increased. On this basis, the air permeability of the coating can be further improved, thereby improving the air permeability and stability of the diaphragm, thereby improving the volatilization effect of the above-mentioned effect of the diaphragm in the embodiment of the present application.

[0117] In addition, the polymer particles in the above embodiments can be solid particles, and of course, they can also be hollow particles. In the embodiments of the present application, solid particles can improve the stability of the polymer particle morphology compared to hollow particles, thereby improving the stability of the separator during battery production and normal operation, including the permeability. For example, the polymer particles will not be deformed due to the squeezing force during battery production or use, thereby preventing the base membrane from blocking pores. Therefore, in the embodiments of the present application, solid polymer particles are relatively preferred compared to hollow polymer particles.

[0118] In some embodiments, the coating layer of the separators described above further contains an inorganic particulate filler. Adding the inorganic particulate filler to the coating layer can, on the one hand, improve the permeability and stability of the coating layer, thereby enhancing the permeability and stability of the separator during battery production and normal operation; on the other hand, it can synergize with the aforementioned polymer particles, improving the separator's liquid storage capacity and mechanical properties such as thermal shrinkage resistance. Furthermore, the inorganic particulate filler is ideally mixed with the aforementioned polymer particles in the coating layer.

[0119] In an embodiment, the content of the inorganic particulate filler in the coating layer can be controlled to achieve a dry weight ratio of the inorganic particulate filler to the polymer particles of (15 to 25): (25 to 35). By controlling the content ratio of the inorganic particulate filler to the polymer particles in the coating layer, the synergistic effect between the two can be enhanced while fully evaporating the respective effects described above, thereby ensuring that the membrane has good air permeability, thermal stability, and liquid storage capacity.

[0120] In the embodiment, the volume distribution particle size D of the inorganic particle filler is v50 is 1 μm to 1.5 μm, and in exemplary embodiments, it can be 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, and other typical but non-limiting particle sizes. By adjusting the inorganic particle filler, it can be compounded with the polymer particle size, such as controlling the D v 50 is in the range of 1μm to 1.5μm, and works together with polymer particles in the aforementioned particle size range to improve the permeability of the separator. Testing has shown that the separator's permeability can reach the permeability performance shown in Table 1 below. Furthermore, when the battery temperature abnormally rises to the melting point of the polymer particles, the inorganic particle filler in this particle size range can fully exert its skeleton function, promoting polymer particle melting and sealing the pores of the base membrane. It also works together with the base membrane to isolate the positive and negative electrodes, reducing the risk of short-circuit thermal runaway.

[0121] In an embodiment, the inorganic particle filler may include at least one of inorganic particles having a dielectric constant of 5 or greater, inorganic particles having ion conductivity but not storing ions, and inorganic particles capable of undergoing electrochemical reactions.

[0122] In an exemplary embodiment, the inorganic material of the inorganic particles having a dielectric constant of 5 or more includes boehmite, aluminum oxide, zinc oxide, silicon oxide, titanium oxide, zirconium oxide, barium oxide, calcium oxide, magnesium oxide, nickel oxide, tin oxide, cerium oxide, yttrium oxide, hafnium oxide, aluminum hydroxide, magnesium hydroxide, silicon carbide, boron carbide, aluminum nitride, silicon nitride, boron nitride, magnesium fluoride, calcium fluoride, barium fluoride, barium sulfate, magnesium aluminum silicate, lithium magnesium silicate, sodium magnesium silicate, bentonite, hectorite, zirconium titanate, barium titanate, Pb(Zr,Ti)O3, Pb 1-m La m Zr 1-n TinO3、Pb(Mg3Nb 2 / 3 )O3-PbTiO3, and at least one of their respective modified inorganic particles, 0<m<1, 0<n<1.

[0123] In an exemplary embodiment, the inorganic material of the inorganic particles having ion conductivity but not storing ions includes Li3PO4, lithium titanium phosphate Li x1 Ti y1 (PO4)3, lithium aluminum titanium phosphate Li x2 Al y2 Ti z1 (PO4)3, (LiAlTiP) x3 O y3 Type glass, lanthanum lithium titanate Li x4 La y4 TiO3, lithium germanium thiophosphate Li x5 Ge y5 P z2 S w , lithium nitride Lix6 N y6 、SiS2 type glass Li x7 Si y7 S z3 and P2S5 glass Li x8 P y8 S z4 At least one of , 0<x1<2, 0<y1<3, 0<x2<2, 0<y2<1, 0<z1<3, 0<x3<4, 0<y3<13, 0<x4<2, 0<y4<3, 0<x5<4, 0<y5<1, 0<z2<1, 0<w<5, 0<x6<4, 0<y6<2, 0<x7<3, 0<y7<2, 0<z3<4, 0<x8<3, 0<y8<3, 0<z4<7;

[0124] In an exemplary embodiment, the inorganic material of the electrochemically reactive inorganic particles includes at least one of lithium-containing transition metal oxides, lithium-containing phosphates, carbon-based materials, silicon-based materials, tin-based materials, and lithium-titanium compounds.

[0125] By carefully selecting the type of inorganic particulate filler material, the aforementioned effects of the inorganic particulate filler are enhanced, further improving the synergistic effect between the inorganic particulate filler and the polymer particles, thereby improving the air permeability and stability of the separators of the present application embodiments, and enhancing the electrochemical performance and safety of the battery. In particular, some of the inorganic particulate fillers of the aforementioned inorganic materials also have excellent liquid absorption and storage capabilities, thereby improving the liquid absorption and storage capabilities of the separator.

[0126] Based on the polymer particles and inorganic particulate fillers described above, in this exemplary embodiment, the polymer particles contained in the coating are low-density polyethylene, specifically low-density polyethylene particles, and further, nonionic low-density polyethylene containing nonionic groups. The low-density polyethylene refers to high-pressure polyethylene (LDPE), specifically polyethylene with a molecular weight of less than 10,000.

[0127] The above-mentioned inorganic particles are compounded with the low-density polyethylene particles to enhance the above-mentioned synergistic effect between the polymer particles and the inorganic particles, thereby improving the air permeability and liquid storage capacity of the coating of the embodiment of the present application, that is, the diaphragm, while increasing the hot melt response rate of the diaphragm, thereby improving the electrochemical performance and safety performance of the battery.

[0128] In some embodiments, the coatings included in the separators of the aforementioned embodiments further include a cured binder. The addition of a binder to the coating effectively enhances the bonding between the polymer particles or further strengthens the bonding between the inorganic particulate fillers, thereby improving the mechanical properties of the coating and the bonding between the coating and the base film, thereby enhancing the stability of the coating, i.e., the separator, including its air permeability.

[0129] In an embodiment, the dry weight ratio of the cured binder to the polymer particles is (15 to 25): (25 to 35). By controlling the binder content in the coating, the mechanical properties of the coating and the adhesion to the base film can be further enhanced, thereby further adjusting the air permeability of the coating, i.e., the membrane.

[0130] In the embodiment, the thermal decomposition temperature of the cured binder is higher than 160°C. By selecting the decomposition temperature characteristic of the binder, the separator has good thermal stability. When the internal temperature of the battery abnormally rises to the melting point of the polymer particles, the separator's barrier effect is enhanced, reducing the risk of thermal runaway of the battery.

[0131] In an embodiment, the binder can be a water-based binder. The water-based binder can be a water-soluble binder or an emulsion binder, among others. In exemplary embodiments, the binder can include at least one of polyvinyl alcohol, polyacrylic acid-polyacrylonitrile copolymer, polyacrylate-polyacrylonitrile copolymer, polyether acrylate, polyurethane, polyacrylate, polycarbonate, polyethylene oxide, rubber, polyacrylic acid, polyacrylonitrile, gelatin, chitosan, sodium alginate, cyanoacrylate, polymerized cyclic ether derivatives, and hydroxyl derivatives of cyclodextrin. These binders can enhance the adhesion between polymer particles or further inorganic particulate fillers, thereby improving the mechanical properties of the coating and the bonding between the coating and the basement membrane. They can further regulate the permeability of the diaphragm and enhance the ability of the polymer particles to melt and seal the pores of the basement membrane when the internal temperature of the battery abnormally rises to the melting point of the polymer particles, thereby improving the electrochemical performance and safety of the battery.

[0132] In an embodiment, when the coating contains both the above-mentioned inorganic particulate filler and a binder, the dry weight ratio of the above-mentioned polymer particles, inorganic particulate filler, and binder in the coating can be (25 to 35): (15 to 25): (15 to 25). By controlling the content ratio of the three components in the coating, the above-mentioned effects of each component and the synergistic effect between the three components are further enhanced, thereby further improving the uniformity of the coating, and improving the air permeability, air permeability uniformity, and mechanical properties of the diaphragm.

[0133] Based on the coating schemes described in the above embodiments, in some embodiments, the coating thickness can be 2 to 5 μm. In exemplary embodiments, the coating thickness can be 2 μm, 3 μm, 4 μm, 5 μm, and other typical but non-limiting thicknesses. By controlling the coating thickness, the content of components such as polymer particles can be controlled, thereby adjusting and enhancing the ability of the polymer particles to fully exert the aforementioned functions, further improving the permeability, stability, and liquid storage capacity of the separator. Furthermore, when the battery temperature rises abnormally, the polymer particles contained in the coating melt and effectively seal the pores of the base membrane, reducing or preventing the risk of thermal runaway.

[0134] Furthermore, the coating included in the separators of the above embodiments can be disposed on one surface of the base membrane, or alternatively, on two opposing surfaces of the base membrane. Based on considerations such as battery energy density and dendrite formation characteristics, in the embodiments, the coating is disposed on one surface of the base membrane, meaning that the coating is not disposed on the opposing surface of the base membrane.

[0135] The base film contained in the separators of the above embodiments can be a battery organic separator. For example, in the embodiments, the thickness of the base film can be 4μm to 7μm. In other embodiments, the air permeability of the base film can be 180s / 100cc to 240s / 100cc. In the exemplary embodiment, the material of the base film includes at least one of non-woven fabric, polyolefin, polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene ether, polyphenylene sulfide, and polyethylene naphthalene. The base films with these characteristics and materials can be combined with the above coating and play a synergistic role on the basis of giving full play to the role of the battery separator, so that the separator has good air permeability and stability, and improves the electrochemical performance and safety performance of the battery.

[0136] In some embodiments, the above-mentioned base membrane can also be a modified base membrane, such as a base membrane modified with at least one modifier such as flame retardants, fiber-like substances, electrochemically inert ceramics, etc., to improve the thermal stability of the base membrane, to cooperate with the above-mentioned coating, and further improve the mechanical properties and safety performance of the diaphragm of the embodiment of the present application.

[0137] Method for preparing diaphragm

[0138] In a second aspect, the present invention provides a method for preparing a diaphragm. The process flow of the method for preparing a diaphragm according to the present invention is shown in FIG1 . The method for preparing a diaphragm according to the present invention may include the following steps:

[0139] S01: providing a basement membrane;

[0140] S02: providing coating slurry;

[0141] S03: coating the coating slurry on at least one surface of the base film, performing a drying process to form a coating layer, and obtaining a separator.

[0142] In the method for preparing the diaphragm of the present embodiment, a coating slurry is applied to form a coating on the surface of the base film, and the coating is then bonded to the surface of the base film. Since the method for preparing the diaphragm of the present embodiment is intended to prepare the diaphragm of the present embodiment, the formed coating contains polymer particles having a melting point of 90°C to 120°C, and optionally 100°C to 115°C.

[0143] The diaphragm preparation method of the embodiment of the present application directly forms a film on the base film with a slurry containing polymer particles with a melting point of 90°C to 120°C, so that the prepared diaphragm is combined with a coating on at least one surface to achieve the coating's modification effect on the base film. Then the coating is the coating contained in the diaphragm of the embodiment of the above text application. Therefore, the diaphragm prepared by the diaphragm preparation method of the embodiment of the present application has the good air permeability and stability or further has a good liquid storage capacity as the diaphragm of the embodiment of the above text application, and can also effectively reduce the risk of thermal runaway of the battery and improve the electrochemical performance and safety performance of the battery. In addition, the process parameters of the diaphragm preparation method of the embodiment of the present application are controllable, and the quality and electrochemical performance of the prepared diaphragm are stable.

[0144] Step S01:

[0145] The base film in step S01 can be the base film contained in the separator of the embodiment of the above-mentioned application. Therefore, the base film can be the base film contained in the separator of the embodiment of the above-mentioned application. As in the embodiment, the thickness of the provided base film can be 4μm to 7μm, and its air permeability can be 180s / 100cc to 240s / 100cc. Its material can include at least one of non-woven fabric, polyolefin, polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene oxide, polyphenylene sulfide, and polyethylene naphthalene.

[0146] Step S02:

[0147] Since the coating slurry in step S02 is a slurry for forming the coating contained in the above text application embodiment diaphragm, the slurry must contain polymer particles and a solvent. In the embodiment, it may further contain an inorganic particle filler and a binder. Therefore, the polymer particles contained in the coating slurry, or the material types and content ratios of the inorganic particle fillers and binders further contained therein are the same as the types and content ratios of the polymer particles, inorganic particle fillers and binders contained in the coating of the above text application embodiment diaphragm. Therefore, in order to save space, the types, content ratios, etc. of polymer particles, inorganic particle fillers and binders will not be described in detail here.

[0148] In order to improve the film-forming quality of the coating slurry, improve the quality of the coating and improve the performance such as air permeability, in one embodiment, the solid content of the coating slurry can be 30wt% to 40wt%; in other embodiments, the viscosity of the coating slurry is 100mPa·s to 1000mPa·s.

[0149] In some embodiments, when the coating slurry in step S02 is formed by mixing polymer particles with inorganic particle fillers and a binder in a solvent; then the mass ratio of polymer particles, inorganic particle fillers, binder and water in the coating slurry can be (25 to 35): (15 to 25): (15 to 25): (20 to 30). This ratio refers to the mixing ratio of the binder to the polymer particles and inorganic particle fillers before curing. By adjusting the ratio of the three, the film-forming quality of the coating slurry is improved, the quality of the formed coating is improved, the permeability and stability of the diaphragm are improved, and the risk of thermal runaway of the battery is reduced.

[0150] The binder may be a pre-cured binder, such as the pre-cured aqueous binder described above. In an exemplary embodiment, the binder may be a pre-cured binder comprising at least one of polyvinyl alcohol, polyacrylic acid-polyacrylonitrile copolymer, polyacrylate-polyacrylonitrile copolymer, polyether acrylate, polyurethane, polyacrylate, polycarbonate, polyethylene oxide, rubber, polyacrylic acid, polyacrylonitrile, gelatin, chitosan, sodium alginate, cyanoacrylate, polymerized cyclic ether derivatives, and hydroxyl derivatives of cyclodextrin.

[0151] For example, in the embodiments, the binder is added in the form of an aqueous binder solution to effectively adjust the viscosity of the coating slurry, improve the dispersion uniformity and stability of the coating slurry components, and improve the film-forming quality of the coating slurry. When the binder is added in the form of an aqueous binder solution, in the embodiments, the viscosity of the aqueous binder solution at 25°C can be 3000mPa·s to 10000mPa·s; in other embodiments, the solid content of the aqueous binder solution is 40wt% to 50wt%. By controlling and adjusting the viscosity of the aqueous binder solution or the solid content at the same time, the positive effect of the binder on the coating slurry can be further enhanced, further improving the slurry stability and dispersibility, and improving the uniformity of the coating.

[0152] In the embodiment, when the polymer particles contained in the coating slurry are polymer particles containing nonionic groups, the polymer particles can be prepared according to a method comprising the following steps:

[0153] Step S021: mixing and reacting polymer precursor particles, an ethoxy-containing polymer, and an initiator to obtain polymer particles containing nonionic groups;

[0154] Step S022: emulsifying the polymer particles containing nonionic groups with a nonionic surfactant to obtain a nonionic polymer emulsion.

[0155] During the reaction process of step S021 , the polymer precursor particles and the ethoxy-containing polymer undergo a polymerization reaction under the action of an initiator, so that the ethoxy-containing group is grafted onto the polymer particles.

[0156] In the embodiment, the polymer precursor particles, the ethoxy-containing polymer, and the initiator are mixed in a mass ratio of (300 to 400): (90 to 125): (20 to 100).

[0157] In an embodiment, the reaction temperature in step S021 can be 130 to 160° C., and the reaction time should be sufficient, such as 2.5 to 3.5 hours at 130 to 160° C. Meanwhile, during the reaction, the molten reactants are stirred to improve the efficiency and uniformity of the reaction.

[0158] By controlling and adjusting the mixing ratio of the reactants in step S021, or further controlling the reaction conditions, on the basis of improving the polymer reaction efficiency, the content of non-ionic groups such as ethoxy groups grafted onto the polymer particles is increased, thereby improving the non-ionic group modification effect of the polymer particles, thereby improving the above effects of the polymer particles, especially improving the surface properties of the polymer particles, improving the dispersibility and dispersion stability of the polymer particles in the coating slurry, thereby improving the membrane quality of the coating slurry to improve the air permeability and stability of the coating, that is, the membrane.

[0159] In an exemplary embodiment, the material of the polymer precursor particles may include at least one of polystyrene, polyolefin, polyimide, melamine resin, phenol resin, cellulose, polyester, polyphenylene sulfide, polyaramid, polyamideimide, and a copolymer of butyl acrylate and ethyl methacrylate.

[0160] The ethoxy-containing polymer may include at least one of allyl polyethylene glycol and bisallyl polyether.

[0161] The initiator may include at least one of di-tert-butyl peroxide and dicumyl peroxide.

[0162] The polymer precursor particles, ethoxylated polymer, and initiator can undergo a polymerization reaction in step S021 to improve the efficiency of graft modification. The ethoxylated polymer can effectively provide ethoxylated nonionic groups to achieve graft modification of the ethoxylated nonionic groups of the polymer precursor particles.

[0163] In step S022, during the emulsification process, the nonionic surfactant and the polymer particles containing nonionic groups form an emulsion in a solvent, wherein the solvent should be water.

[0164] In addition, the mixing ratio of the nonionic surfactant and the polymer particles containing nonionic groups, as well as the amount of added aqueous solvent, can be controlled to adjust and control the relevant properties of the nonionic polymer emulsion, such as viscosity, solid content, pH value, etc., thereby improving the dispersion uniformity and stability of the polymer particles in the coating slurry, thereby improving the above-mentioned effect of forming the coating and improving the electrochemical performance and safety performance of the prepared separator. For example, by controlling and adjusting the conditions of the emulsification treatment in step S022, the nonionic polymer emulsion has at least one of the following properties:

[0165] (1) The viscosity of the nonionic polymer emulsion at 25° C. is 10 mPa·s to 100 mPa·s;

[0166] (2) the solid content of the nonionic polymer emulsion is 35 wt % to 40 wt %;

[0167] (3) The pH value of the nonionic polymer emulsion is 5 to 6.

[0168] In an embodiment, the polymer particles and the non-ionic surfactant can be mixed and emulsified in a mass ratio of (4 to 6): 1, and a demonstration example can be 4.5: 1, which can effectively adjust the viscosity and solid content of the non-ionic polymer emulsion, thereby improving the dispersibility of the polymer particles and improving the uniformity and stability of the coating slurry.

[0169] In some embodiments, the nonionic surfactant may include a molecular structure of

[0170] Wherein, R1 is a carbon chain alkyl group. In an exemplary embodiment, when it is a carbon chain alkyl group, R1 is a long carbon chain alkyl group of C12 to C18.

[0171] R2 is a hydrophilic group. In an exemplary embodiment, R2 is at least one of a carboxyl group, an amine group, an aldehyde group, an alcohol group, an amino group, and an amide group.

[0172] n is a positive integer from 3 to 20. In the examples, n can be a typical but non-limiting positive integer such as 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20.

[0173] In an exemplary embodiment, the nonionic surfactant includes at least one of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester, castor oil polyoxyethylene ether, fatty amine polyoxyethylene ether, sorbitan fatty acid ester, and polyoxyethylene sorbitan fatty acid ester.

[0174] By selecting the type of nonionic surfactant, the stability of the nonionic polymer emulsion can be improved, its dispersibility in the coating slurry can be improved, and thus the dispersion uniformity and stability of the polymer particles can be improved.

[0175] In addition, there is no specific order between step S01 and step S02 above. The order can be adjusted according to actual production, or they can be performed simultaneously.

[0176] Step S03:

[0177] The coating slurry is applied to the base film in step S02 to form a wet film, i.e., the coating layer before drying. The coating method is not limited to any method capable of forming a film of the coating slurry on the base film, and is within the scope of the embodiments disclosed herein. Examples include, but are not limited to, brushing, roller coating, and spraying. Furthermore, the coating process conditions can be further adjusted to optimize the film quality, thickness, and air permeability.

[0178] In the embodiment, the coating slurry in step S02 can be coated at a rate of 50 m / min to 100 m / min. This coating rate can improve the quality of the coating, adjust the air permeability and thickness, etc.

[0179] The drying process is primarily intended to remove the solvent from the wet film. Based on the melting temperature range of the polymer particles contained in the coating slurry, the drying process should be performed at a temperature below the melting temperature of the polymer particles and at a temperature that ensures coating quality and stability. For example, in the embodiment, the drying process temperature can be 60°C to 70°C. In exemplary embodiments, typical but non-limiting temperatures such as 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C, and 70°C can be used. Within this drying process temperature range, the drying time should be sufficient, such as a drying process time of 1 to 3 minutes.

[0180] Battery

[0181] In a third aspect, an embodiment of the present application provides a battery comprising a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, wherein the separator is the separator of the embodiment of the present application.

[0182] In the embodiments, the separator is coated only on one surface, with the coated surface facing the negative electrode. By orienting the coating toward the negative electrode, the separator can fully utilize the functions described in the embodiments of the previous application, further reducing metal deposition and dendrite formation on the negative electrode, thereby improving battery safety. Furthermore, by only coating the separator on one surface, the overall thickness of the separator can be effectively reduced, thereby increasing the battery's energy density.

[0183] In some embodiments, the battery of the present application can be a secondary battery. When the battery of the present application is a secondary battery, it includes a positive electrode, a separator, and a negative electrode. Specifically, the negative electrode of the secondary battery is the negative electrode of the embodiment described above, and the negative electrode contains the modified artificial graphite of the embodiment described above.

[0184] In this way, the battery of the embodiment of the present application, specifically the secondary battery, has high energy density, high rate capability and good cycle stability.

[0185] In an embodiment, the secondary battery of the present application may include any one of a battery cell, a battery module, and a battery pack.

[0186] A battery cell is a structure that includes a battery housing and a cell encapsulated within the housing. The shape of a battery cell is not particularly limited and can be cylindrical, square, or any other shape. A square-shaped battery cell 10 is shown in FIG2 .

[0187] In some embodiments, as shown in Figure 3, the outer packaging of the battery cell 10 may include a shell 11 and a cover plate 13. The shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the cover plate 13 is used to cover the opening to close the receiving cavity. The positive electrode, diaphragm and negative electrode contained in the secondary battery of the embodiment of the present application can be formed into an electrode assembly 12 through a winding process and / or a lamination process. The electrode assembly 12 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 12. The number of electrode assemblies 12 contained in the battery cell 10 can be one or more, which can be adjusted according to actual needs.

[0188] The preparation method of the battery cell 10 is well known. In some embodiments, the positive electrode, separator, negative electrode, and electrolyte can be assembled to form the battery cell 10. As an example, the positive electrode, separator, and negative electrode can be wound or laminated to form the electrode assembly 12. The electrode assembly 12 is placed in an outer package, dried, and then injected with electrolyte. The battery cell 10 is then vacuum packaged, allowed to stand, formed, and shaped.

[0189] A battery module is assembled from the battery cells 10 , that is, it may contain a plurality of battery cells 10 , and the specific number can be adjusted according to the application and capacity of the battery module.

[0190] In some embodiments, FIG4 is a schematic diagram of an exemplary battery module 20. As shown in FIG4 , in the battery module 20, multiple battery cells 10 may be arranged sequentially along the length of the battery module 20. Of course, any other arrangement is also possible. Furthermore, the multiple battery cells 10 may be secured together using fasteners.

[0191] Optionally, the battery module 20 may further include a housing having an accommodation space, and the plurality of battery cells 10 may be accommodated in the accommodation space.

[0192] A battery pack is assembled from the battery cells 10 described above, and may contain multiple battery cells 10, wherein multiple battery cells 10 may be assembled into the battery module 20 described above. The specific number of battery cells 10 or battery modules 20 contained in a battery pack may be adjusted according to the application and capacity of the battery pack.

[0193] In the embodiment, Figures 5 and 6 are schematic diagrams of an exemplary battery pack 30. The battery pack 30 may include a battery box and multiple battery modules 20 disposed within the battery box. The battery box includes an upper box body 31 and a lower box body 32. The upper box body 31 covers the lower box body 32 and forms an enclosed space for accommodating the battery modules 20. The multiple battery modules 20 may be arranged in any manner within the battery box.

[0194] Electrical devices

[0195] In a sixth aspect, embodiments of the present application further provide an electrical device comprising the battery of the aforementioned embodiments, which may further comprise a secondary battery. The battery can serve as both a power source and an energy storage unit for the electrical device. Consequently, the electrical device of the embodiments of the present application has a long standby or battery life.

[0196] Electrical devices may include, but are not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, energy storage systems, etc. These electrical devices may use secondary batteries, battery modules, or battery packs based on their usage requirements.

[0197] Figure 7 is a schematic diagram of an exemplary electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of this device, a battery pack or battery module may be used.

[0198] As another example, the electric device may be a mobile phone, a tablet computer, a laptop computer, etc. Such an electric device is usually required to be lightweight and thin, and may use a secondary battery as a power source.

[0199] Example

[0200] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.

[0201] 1. Diaphragm and its preparation method embodiment

[0202] Example A1

[0203] This embodiment provides a separator and a method for preparing the same. The separator comprises a PE base film and a coating bonded to one surface of the PE base film. The PE base film is 7 μm thick, and the coating is 2 μm thick. The coating contains nonionic polyethylene wax particles, and the polymer particles contain ethoxy groups. The melting points of the polymer particles are shown in Table 1 below.

[0204] The diaphragm preparation method of this embodiment includes the following steps:

[0205] S1. Preparation of coating slurry:

[0206] S11. Preparation of polymer particles:

[0207] a. According to the polyethylene wax: allyl polyethylene glycol: initiator = 300:100:20 mass ratio of polyethylene wax, allyl polyethylene glycol, di-tert-butyl peroxide initiator was mixed and heated to melt and stirred uniformly, and the intermediate product was obtained after a constant temperature of 160 ℃ and 3h;

[0208] b. The intermediate product and the nonionic emulsifier were mixed in a mixing ratio of 4.5:1, heated to melt, stirred to form a uniform emulsion, and water was added to adjust the viscosity to an appropriate range of 10mPa·s to 100mPa·s and a solid content of 35% to 40% to obtain a nonionic polyethylene wax emulsion;

[0209] S12. Prepare coating slurry:

[0210] A nonionic polyethylene wax emulsion, polymethyl methacrylate, boehmite, and water are mixed in a weight ratio of polymer particles: polymethyl methacrylate: boehmite: water = 25%: 25%: 20%: 30%. All materials are added to a double planetary stirring tank, and then stirred for 3 hours at an orbital speed of 30 rpm and an autorotation speed of 2000 rpm, with vacuum defoaming throughout the process. The viscosity of the coating slurry is controlled between 500 mPa·s and 800 mPa·s.

[0211] S2. Film formation treatment of coating slurry on the surface of base film:

[0212] The coating slurry in step S1 was coated on one side of a 7 μm PE base film to form a wet film, and then dried to form a 2 μm coating on one side of the PE base film; wherein the coating slurry coating speed was 80 m / min, the oven temperature was 65° C., and the total drying time was 2 min.

[0213] Example A2

[0214] This embodiment provides a separator and a method for preparing the same. The separator of this embodiment is identical to the separator of Example A1 except for the different melting points of the polymer particles contained in the coating. The melting point of the polymer particles contained in the coating of the separator of this embodiment is 100°C as shown in Table 1.

[0215] The diaphragm of this embodiment was prepared by referring to the diaphragm preparation method in Example A1.

[0216] Example A3

[0217] This embodiment provides a separator and a method for preparing the same. The separator of this embodiment is identical to the separator of Example A1 except that the polymer particles contained in the coating have different melting points. The melting point of the polymer particles in this embodiment is 120° C. as shown in Table 1.

[0218] Example A4

[0219] This embodiment provides a separator and a method for preparing the same. The separator in this embodiment is identical to the separator in Example A1, except for the polymer particles contained in the coating and their melting point. Specifically, the polymer particles in this embodiment are made of a low-melting-point polyester, with a melting point of 90°C as shown in Table 1.

[0220] Example A5

[0221] This embodiment provides a separator and a method for preparing the same. The separator in this embodiment is identical to the separator in Example A1, except that the coating layer contains no inorganic particles. The separator coating is formed using the coating method described in Example A1 using a coating slurry having a mass ratio of polymer particles: polymethyl methacrylate: boehmite: water of 45%:25%:0%:30%.

[0222] Example A6

[0223] This embodiment provides a separator and a method for preparing the same. The separator of this embodiment is identical to the separator of Example A1 except for the polymer particles contained in the coating. Specifically, the polymer particles in this embodiment are polyethylene wax particles with a melting point of 100° C. as shown in Table 1.

[0224] Example A7

[0225] This embodiment provides a diaphragm and a method for preparing the same. The diaphragm of this embodiment is identical to the diaphragm of Example A1 except for the coating thickness. Specifically, the coating thickness of the diaphragm of this embodiment is 5 μm.

[0226] Comparative Example A1

[0227] This comparative example provides a separator, which is different from the separator in Example A1 in that the separator coating does not contain polymer particles. The remaining features are identical.

[0228] The preparation method for the diaphragm in this comparative example was similar to that in Example A1. The difference from Example A1 was that the coating slurry was prepared by mixing the components of the coating slurry in a mass ratio of polymer particles: polymethyl methacrylate: boehmite: water = 0%: 25%: 45%: 30%. The steps and process conditions were the same.

[0229] Comparative Example A2

[0230] This comparative example provides a separator that, compared to the separator in Example A1, has identical characteristics except for the polymer particles contained in the coating. Specifically, the polymer particles in this comparative example are made of a low-melting-point polyester, with a melting point of 85°C as shown in Table 1. The S12 coating slurry preparation proceeds directly without the S11 modification step.

[0231] Comparative Example A3

[0232] This comparative example provides a separator that, compared to the separator in Example A1, has identical characteristics except for the polymer particles contained in the coating. Specifically, the polymer particles in this comparative example are made of polyphenylene sulfide, having a melting point of 125°C as shown in Table 1. The S12 coating slurry preparation proceeds directly without the S11 modification step.

[0233] Comparative Example A4

[0234] This comparative example provides a separator and a preparation method thereof. The separator of this comparative example is identical to the separator of Example A1 except that the melting point of the polymer particles contained in the coating is different, and the melting point is 125° C. as shown in Table 1.

[0235] 2. Secondary Battery Cell Example

[0236] Example B1 to Example B7 and Comparative Example B1 to Comparative Example B4;

[0237] Embodiments B1 to B7 and Comparative Examples B1 to B4 each provide a secondary battery cell, each comprising a positive electrode, a separator, and a negative electrode forming a battery cell, and also comprising an electrolyte. The separators provided in Embodiments A1 to A7 and Comparative Examples A1 to A4 are the separators provided in the secondary battery embodiments B1 to B7 and Comparative Examples B1 to B4, respectively. The separator in Embodiment A1 serves as the separator in the battery cell of Secondary Battery Embodiment B1, the separator in Embodiment A2 serves as the separator in the battery cell of Secondary Battery Embodiment B2, and so on. The separator in Comparative Example A4 serves as the separator in the battery cell of Comparative Example B4.

[0238] The positive electrode was prepared as follows:

[0239] Using methyl pyrrolidone (NMP) as solvent, LiNi 0.8 Co 0.1 Mn 0.1 O2, carbon nanotubes (CNT), and binder (PVDF) were mixed in a mass ratio of 97:2:1 to prepare a positive electrode slurry with a solid content of 80%. The positive electrode slurry was evenly coated on aluminum foil and double-sided coating was performed, where the surface density of each single side was 0.131g / 1540.25mm 2 After being fully dried, cold pressed and cut, the positive electrode sheet is obtained as the positive electrode.

[0240] Negative electrode: Using water as solvent, artificial graphite, conductive agent SP, dispersant (CMC), and binder (SBR) are mixed in a mass ratio of 96:1:1:2 to prepare a negative electrode slurry with a solid content of 58%. The positive electrode slurry is evenly coated on aluminum foil and double-sided coating is performed, where the surface density of each single side is 0.065g / 1540.25mm 2 After being fully dried, cold pressed and cut, the negative electrode sheet is obtained as the negative electrode.

[0241] Electrolyte: Ethylene carbonate (EC) and diethyl carbonate (DEC) were mixed at a volume ratio of 1:1 at room temperature, and LiPF6 was added to the mixed solution to obtain a solution with a concentration of 1 mol / L as the electrolyte;

[0242] Secondary battery assembly: In a low-humidity constant temperature room, the positive and negative electrode sheets prepared as above are stacked and wound in the order of "positive electrode-separator-negative electrode" to form a bare cell, which is then filled with electrolyte to assemble into a lithium-ion secondary battery.

[0243] Performance tests of diaphragms and secondary battery cells

[0244] The separators and secondary battery cells provided in the above embodiments and comparative examples were tested respectively.

[0245] 1. Diaphragm performance test:

[0246] 1.1 The membranes in Examples A1 to A7 and Comparative Examples A1 to A4 were tested for the relevant properties listed in Table 1. Each test method was performed in accordance with national standards (if no national standards were used, the industry standard methods were used). For example, air permeability was tested using a membrane air permeability tester in accordance with the reference standard GB / T 36363-2018; melting point was measured using a universal differential scanning calorimeter (DSC) method in accordance with the standard ISO 11357-3-2018; molecular weight was measured using gel permeation chromatography (GPC) in accordance with the GBT 27843-2011 method for detecting low molecular weight components in polymers; unless otherwise specified, the volume distribution particle size Dv50 of the organic particles in this application was determined using a particle size analyzer-laser diffraction method. Specifically, the measurement was performed using a laser diffraction scattering particle size analyzer (Mastersizer 3000 laser particle size analyzer) in accordance with the manufacturer's instructions, with reference to the standard GB / T 19077-2016.

[0247] The measured results are shown in Table 1 below.

[0248] 1.2 The separators of Examples A1 to A7 and Comparative Examples A1 to A4 were subjected to scanning electron microscopy (SEM) analysis after being heated at room temperature (25°C) and at 120°C for 15 minutes. SEM photographs of the separator in Example A1 after heating at room temperature and 120°C for 15 minutes are shown in Figures a and b, respectively, and SEM photographs of the separator in Comparative Example A1 after heating at room temperature and 130°C for 15 minutes are shown in Figures a and b, respectively, in Figures 9.

[0249] Table 1

[0250]

[0251]

[0252] In conjunction with Figures 8 and 9, it can be seen from the membrane-related performance data in Table 1, and by comparing the air permeability of Examples A1 to A7 and Comparative Example A1 in Table 1 at room temperature and after heating at 120°C for 15 minutes, it can be seen that when the ambient temperature of the membrane in the embodiment of the present application is lower than the melting point of the polymer particles contained in the coating, the membrane has good air permeability. When the ambient temperature is higher than the melting point of the polymer particles contained in the coating, the polymer particles contained in the membrane coating can melt and seal the pores of the base membrane, causing the membrane to lose its air permeability, thereby effectively terminating metal ion migration or positive and negative electrode crosstalk reactions within the battery, thereby improving battery safety performance.

[0253] Comparing the coating slurry uniformity of Examples A2 and A6 in Table 1 shows that the introduction of nonionic groups improves the dispersion of polymer particles during the coating slurry preparation, resulting in a more uniform and agglomerated coating. Due to the presence of agglomeration in the slurry, the air permeability of the A6 separator varied at different locations after heating at 120°C for 15 minutes. Therefore, when fabricating the battery of Example B6, it was necessary to select locations with uniform coating.

[0254] 2. Secondary battery cell performance test:

[0255] 2.1 Hot box test of secondary battery cells

[0256] The secondary battery cells from Examples B1 to B7 and Comparative Examples B1, B3, and B4 were fully charged and subjected to hot box testing at 100% SOC for 30 minutes at the various temperatures listed in Table 2. After the testing, the negative electrode sheets were disassembled and the metal element content within them was measured using ICP. The results of the total metal content (excluding lithium) are shown in Table 2 below.

[0257] Table 2

[0258]

[0259] It can be seen from Examples B1 to B4 and Comparative Example B1 in Table 2 that the separators of the embodiments of the present application can effectively stop the migration of metal ions in the battery after taking effect.

[0260] It can be seen from Examples B1 to B4 and Comparative Example B4 in Table 2 that if the melting point of the polymer particles is too high, the separator will take effect later and will not be able to terminate the metal ion migration or positive and negative electrode crosstalk reaction in the battery in time in the early stage of battery thermal runaway.

[0261] 2.2 Air permeability of the diaphragm after secondary battery monomer injection

[0262] After the secondary battery cells in the above-mentioned Examples B1 to B7 and Comparative Examples B1 to B4 were injected and formed under the same injection and formation conditions, the batteries were disassembled to obtain each diaphragm. The air permeability of each diaphragm was tested according to the diaphragm permeability method in Section 1.1 above. The measured results are shown in "After battery injection and high temperature (85°C) aging" in Table 1.

[0263] Comparing the air permeability after injection aging of Example A4 and Comparative Example A2 in Table 1, it can be seen that if the melting point of the polymer particles is close to the aging temperature, the diaphragm will be impermeable during the normal battery production process, and the battery cannot be produced normally.

[0264] 2.3 Secondary battery cell cycle test

[0265] The secondary battery cells in the above-mentioned Examples B1 to B7 and Comparative Example B1 were subjected to cycle tests at 25° C. and 1C / 1C conditions, and the test results are shown in Table 3.

[0266] Table 3

[0267]

[0268] It can be seen from Examples B1 to B5 and B7 and Comparative Example B1 in Table 3 that the diaphragm of the present application can maintain good air permeability during battery production and normal use, and does not affect the charge and discharge cycle performance of the battery.

[0269] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some or all of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A diaphragm, characterized in that: The invention comprises a base film and a coating layer arranged on at least one surface of the base film, wherein the coating layer contains polymer particles, and the melting point of the polymer particles is 90° C. to 120° C., and optionally 100° C. to 115° C.

2. The diaphragm according to claim 1, characterized in that The polymer particles satisfy at least any one of the following conditions (1) to (5): (1) Volume distribution particle size D of the polymer particles v 50 is 0.1μm to 5μm, and can be 0.3μm to 3μm; (2) The morphology of the polymer particles includes at least one of chain, spherical, quasi-spherical, fibrous, tubular, rod-shaped, amorphous, and pyramidal; (3) The polymer of the polymer particles contains a nonionic group, and optionally, the nonionic group includes at least one of an ethoxy group, a hydroxyl group, and a carboxylate group; (4) The weight average molecular weight of the polymer material of the polymer particles is 1000 to 10000, and can be optionally 1500 to 8000; (5) The polymer includes at least one of polystyrene, polyolefin, polyimide, melamine resin, phenol resin, cellulose, polyester, polyphenylene sulfide, polyaromatic amide, polyamideimide, copolymer of butyl acrylate and ethyl methacrylate and their respective modified polymers.

3. The diaphragm according to any one of claims 1 to 2, characterized in that: The coating also includes an inorganic particulate filler.

4. The diaphragm according to claim 3, characterized in that The inorganic particle filler at least satisfies any one of the following conditions: The dry weight ratio of the inorganic particle filler to the polymer particles is (15 to 25): (25 to 35); The volume distribution particle size D of the inorganic particle filler v 50: 1 μm to 1.5 μm; The inorganic particle filler includes at least one of inorganic particles having a dielectric constant of 5 or more, inorganic particles having ion conductivity but not storing ions, and inorganic particles capable of electrochemical reaction.

5. The diaphragm according to claim 4, characterized in that The polymer contained in the polymer particles is low-density polyethylene, which can be non-ionic low-density polyethylene.

6. The diaphragm according to any one of claims 1 to 5, characterized in that: The coating also includes a binder.

7. The diaphragm according to claim 6, characterized in that The binder satisfies at least one of the following conditions: The dry weight ratio of the binder to the polymer particles is (15 to 25): (25 to 35); The binder is a water-based binder; The thermal decomposition temperature of the binder is higher than 160°C; The binder includes at least one of polyvinyl alcohol, polyacrylic acid-polyacrylonitrile copolymer, polyacrylate-polyacrylonitrile copolymer, polyether acrylate, polyurethane, polyacrylate, polycarbonate, polyethylene oxide, rubber, polyacrylic acid, polyacrylonitrile, gelatin, chitosan, sodium alginate, cyanoacrylate, polymerized cyclic ether derivatives, and hydroxyl derivatives of cyclodextrin.

8. The diaphragm according to any one of claims 1 to 7, characterized in that: The coating thickness is 2 μm to 5 μm; and / or The coating layer is disposed on one surface of the base film.

9. The diaphragm according to any one of claims 1 to 8, characterized in that: The base film satisfies at least one of the following conditions: The thickness of the base film is 4 μm to 7 μm; The air permeability of the base film is 180s / 100cc to 240s / 100cc; The material of the base film includes at least one of non-woven fabric, polyolefin, polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene ether, polyphenylene sulfide, and polyethylene naphthalene.

10. A method for preparing a diaphragm, characterized in that: The steps include: providing a basement membrane; Providing a coating slurry, wherein the coating slurry contains polymer particles, and the melting point of the polymer particles is 90° C. to 120° C., and optionally 100° C. to 115° C.; The coating slurry is coated on at least one surface of the base film, and a coating is formed after drying to obtain a separator.

11. The preparation method according to claim 10, characterized in that: The coating slurry is formed by mixing polymer particles, inorganic particle fillers and a binder in a solvent; wherein the mass ratio of the polymer particles, the inorganic particle filler and the binder in the coating slurry is (25 to 35): (15 to 25): (15 to 25); and / or The solid content of the coating slurry is 30wt% to 40wt%; and / or The coating slurry has a viscosity of 100 mPa·s to 1000 mPa·s at 25°C.

12. The preparation method according to claim 10 or 11, characterized in that: When the polymer particles are polymer particles containing nonionic groups, the polymer particles are prepared by a method comprising the following steps: The polymer precursor particles, the ethoxy-containing polymer and the initiator are mixed and reacted to obtain polymer particles containing nonionic groups; The polymer particles containing nonionic groups are emulsified with a nonionic surfactant to obtain a nonionic polymer emulsion.

13. The preparation method according to claim 12, characterized in that: The polymer precursor particles, the ethoxy-containing polymer and the initiator are mixed in a mass ratio of (300 to 400): (90 to 125): (20 to 100); and / or The material of the polymer precursor particles includes at least one of polystyrene, polyolefin, polyimide, melamine resin, phenol resin, cellulose, polyester, polyphenylene sulfide, polyaramid, polyamideimide, and copolymer of butyl acrylate and ethyl methacrylate; and / or The ethoxy-containing polymer comprises at least one of allyl polyethylene glycol and bisallyl polyether; and / or The initiator comprises at least one of di-tert-butyl peroxide and dicumyl peroxide; and / or The reaction temperature is 130°C to 160°C; and / or The polymer particles and the nonionic surfactant are emulsified in a mass ratio of (4 to 6):

1.

14. The preparation method according to claim 12 or 13, characterized in that: The nonionic polymer emulsion satisfies at least any one of the following conditions (1) to (4): (1) The viscosity of the nonionic polymer emulsion at 25° C. is 10 mPa·s to 100 mPa·s; (2) The solid content of the nonionic polymer emulsion is 35wt% to 40wt%; (3) The pH value of the nonionic polymer emulsion is 5 to 6; (4) The nonionic surfactant includes a molecular structure of Wherein, R1 is a carbon chain alkyl group, R2 is a hydrophilic group, and n is a positive integer from 3 to 20.

15. The preparation method according to claim 14, characterized in that: The carbon chain alkyl is a long carbon chain alkyl of C12 to C18; and / or The R2 is at least one of a carboxyl group, an amine group, an aldehyde group, an alcohol group, an amino group, and an amide group.

16. The preparation method according to any one of claims 12 to 15, characterized in that: The nonionic surfactant includes at least one of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester, castor oil polyoxyethylene ether, fatty amine polyoxyethylene ether, sorbitan fatty acid ester and polyoxyethylene sorbitan fatty acid ester.

17. The preparation method according to any one of claims 11 to 16, characterized in that: The binder is added in the form of a binder aqueous solution, and the binder aqueous solution has at least one of the following conditions: The viscosity of the binder aqueous solution at 25° C. is 3000 mPa·s to 10000 mPa·s; The solid content of the binder aqueous solution is 40 wt % to 50 wt %.

18. The preparation method according to any one of claims 10 to 17, characterized in that: The coating slurry is applied at a rate of 50 m / min to 100 m / min; and / or The drying temperature is 60°C to 70°C; and / or The drying time is 1 min to 3 min.

19. A battery, characterized in that: The invention comprises a positive electrode, a negative electrode and a separator stacked between the positive electrode and the negative electrode, wherein the separator is the separator according to any one of claims 1 to 9 or the separator prepared by the preparation method according to any one of claims 10 to 18.

20. The battery according to claim 19, characterized in that The coating layer is disposed on one surface of the separator, and the coating layer faces the negative electrode.

21. An electrical device, characterized in that: The electrical device comprises the battery as claimed in claim 19 or 20, and the battery is used to provide electrical energy.

Citation Information

Cited By

  • Flame-retardant diaphragm, preparation method thereof and secondary battery

    CN122552754A